NURTURING YOUNG MINDS: THE BENEFITS AND BARRIERS OF SECOND LANGUAGE LEARNING - Inggrid Yossi Anna Sianipar; Bernieke Anggita Ristia Damanik (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In the areas of education, linguistics, and cognitive science, the process of learning a second language (L2) throughout childhood has been widely studied and debated. Because of the brain's increased flexibility, which enables more flexibility in taking in and remembering language information, childhood is frequently regarded as an essential age for language learning. Speaking more than one language has become essential in many academic, professional, and cultural situations as civilizations become more interconnected through globalization. With a focus on cognitive, social, and cultural aspects, this paper aims to explore all of the benefits of early exposure to a second language while also addressing the main challenges that students may face. Learning a second language has several cognitive benefits, including improved memory storage, improved mental flexibility, and improved problem-solving abilities. Socially, bilingualism helps kids navigate multicultural settings more easily by fostering better communication skills, empathy, and a greater understanding of cultural diversity. Early exposure to a second language helps broaden a child's perspective and foster tolerance and inclusivity by assisting them in comprehending and appreciating the customs, beliefs, and viewpoints of many societies.